Diabetic Nephropathy Determinant Factor in Diabetes Mellitus at RSUD Dr. M. Soewandhie Surabaya - Putri, Rahmadany Isya (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTNon communicable diseases are an important health problem related with the shift in the pattern of death cause, which is from infectious diseases to non-infectious diseases. Diabetes mellitus (DM) ranked 5 of the top 10 causes of non-infectious diseases in hospitals in Indonesia. If not properly controlled, DM can lead to chronic complications such as Diabetic Nephropathy (DN). This study, conducted at Internal Medicine Clinic, Outpatient Care, Dr. M. Soewandhie Hospital Surabaya, in June-July 2014, aimed to analyze correlation between non-clinical factors according to the concept of Hendrik L. Blum, such as compliance to treatment, education level, income, and social support for the incidence of DN in DM patients. This study was an observational analytic study with case-control design. Case samples in this study were DM patients who experienced DN complications and undergoing treatment at Internal Medicine Clinic, Outpatient Care, Dr. M. Soewandhie Hospital Surabaya, by 36 respondents. Control samples in this study were diabetic patients who did not experience complications DN undergoing treatment at Internal Medicine Clinic, Outpatient Care, Dr. M. Soewandhie Hospital Surabaya, by 36 respondents. Samples were taken by using a convenience sampling method. Relation streght analysis between dependent and independent variables used Contingency Coefficient by Chi Square test with 95% Confidence Interval (Î±=0.05). To determine the amount of risk between dependent and independent variables, we used OR (odds ratio) calculation. The results showed that non-compliance to treatment (OR=2.8) with contigency coefficient 0.243, low education (OR=1.5) with contigency coefficient 0.091, income < District Minimum Wage (OR=1.21) with contigency coefficient 0.036, and not receiving social support (OR=1.65) with contigency coefficient 0.117. In conclusion, compliance to treatment, education level, income, and social support affect the incidence of DN in DM patients.Keywords: compliance to treatment, education level, income, social support, diabetic nephropathy